Role of Testosterone on Waist to Hip Ratio in Women with Hirsutism - Abdulsamie H. Alta'ee (Journal of Global Pharma Technology, 2018)
Hirsutism is a series problem faced women in the present days. It is usually associated with elevated levels of androgen hormones. This study aims to investigate the role of testosterone in the waist-to-hip ratio (WHR), and body mass index (BMI) of 54 women with hirsutism and 54 healthy women match in age, in a case control study. Free testosterone and thyroid stimulated hormone (TSH) were determined using ELISA technique. WTR, BMI and hirsutism score were examined in the study groups. Free testosterone, TSH, WTR, BMI and hirsutism score found to be significantly increased when compared with control group. The result of the present study may hypothesize that testosterone has a central role in the path physiological changes occur in hirsutism, such as fat storage pattern and as consequence the HWR and the stimulation effect to induce TSH and its effect on hair growth. Keywords: Hirsutism, WTR, Testosterone, TSH, BMI.